Fungsi Metode terhadap Pencapaian Tujuan dalam Komponen Pembelajaran - Isnawardatul Bararah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Internal and external factors are factors that influence students in learning achievement. Among the internal factors that can be internalized by students in learning, achievement includes attitudes towards learning, interest, and motivation to learn, concentration in learning, in addition, there are also external factors which include: teachers as coaches in the learning process, learning infrastructure and facilities, assessment, environment social welfare of students both at school and at home as well as the curriculum applied at school. The stage of learning achievement will be easily achieved if a teacher is wise in determining the use of learning methods. These conditions will affect student achievement in responding to each component of the learning material taught by the teacher for all subjects. Although not all teachers use the same learning method approach, on the other hand, a teacher is also required to master complex learning materials so that the transfer of knowledge process in the classroom represents all learning materials as a whole.